2022
DOI: 10.1021/acs.orglett.2c03483
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Alkyne–Oximium Cyclization for the Stereoselective Synthesis of Isoxazolidine

Abstract: A TMSOTf-mediated highly diastereoselective synthesis of isoxazolidine bearing three contiguous stereocenters is described. This method utilizes O-propargyl hydroxylamines as a novel building block for the rapid assembly of the isoxazolidines via alkyne−oximium cyclization. The strategy could be used in the synthesis of enantiomerically enriched isoxazolidines. Reductive cleavage of the N−O bond efficiently gives the corresponding 1,3-aminodiols with precise control over all stereocenters formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In this context, Gharpure reported a TMSOTf‐promoted alkyne oximium cyclization reaction O ‐propargylated hydroxylamines 11 for the diastereoselective synthesis of isoxazolidine 12 in good yield and excellent diastereoselectivities (dr >19 : 1) (scheme 5). [36] The limitation and scope of the reaction were studied with different aldehydes and alkyl substituents at the carbon α to the oxygen of propargyl hydroxylamine and substituents on alkynes. In general, it was observed that both alkyl and aryl aldehydes reacted on expected lines to furnish corresponding isoxazolidine 12 in excellent diastereoselectivities.…”
Section: Carboxygenationmentioning
confidence: 99%
“…In this context, Gharpure reported a TMSOTf‐promoted alkyne oximium cyclization reaction O ‐propargylated hydroxylamines 11 for the diastereoselective synthesis of isoxazolidine 12 in good yield and excellent diastereoselectivities (dr >19 : 1) (scheme 5). [36] The limitation and scope of the reaction were studied with different aldehydes and alkyl substituents at the carbon α to the oxygen of propargyl hydroxylamine and substituents on alkynes. In general, it was observed that both alkyl and aryl aldehydes reacted on expected lines to furnish corresponding isoxazolidine 12 in excellent diastereoselectivities.…”
Section: Carboxygenationmentioning
confidence: 99%
“…Later in 2021, Frontier group disclosed an interesting two‐step Prins‐Nazarov cyclization for the synthesis of polycyclic ring system via trapping of N ‐acyliminium ion by tethered alkyne chain [11] . Very recently, we demonstrated that alkyne oximium cyclization can be used for expeditious assembly of isoxazolidines [10c] . Herein, we now disclose a general approach for the synthesis of pyrrolo/pyrido[2,1‐a]isoindoles via alkyne iminium ion cyclization of vinylogous carbamates.…”
Section: Introductionmentioning
confidence: 97%
“…Over the years, our group has developed various strategies for the synthesis of heterocyclic compounds using alkynes. [15] Recently, we demonstrated the basemediated synthesis of cyclic, spiro-heterocyclic and bridged bicyclic β-ketosulfones via a hydroalkoxylation-initiated cascade of sulfone-tethered aryl alkynols (Scheme 1, eq. 1c).…”
mentioning
confidence: 99%